A Web-Based Information System for Detainee Data Management at Badan Narkotika Nasional (BNN) in Jambi Province - Zikri Saputra; Sukma Puspitorini; Teuku Djauhari (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
This research is based on the problem of manual recording which is at risk of data loss and misuse. This research aims to develop a web-based information system that facilitates the management of prisoner data, detainees, and evidence at the National Narcotics Agency (BNN) of Jambi Province. By applying the Research and Development (R&D) method and the Waterfall approach. The features implemented include input of prisoner data, prisoner data management, and recording of evidence. The test results show that the system works well and makes it easier for officers to record and manage data. The system also provides output in the form of reports which will later make it easier for officers to report starting from prisoner data, detainee data and confiscated evidence data. The system is built into a website-based application. It is hoped that this system will not only replace manual methods, but also make a real contribution in supporting BNN's task in eradicating narcotics abuse. The research findings can be a reference for the development of information systems in other agencies with similar needs. Keywords: Human Resource Digitalization Generative AI Talent Management Performance Monitoring Executive Information Systems.